If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10(x + -1) = 4(5x + -10) Reorder the terms: 10(-1 + x) = 4(5x + -10) (-1 * 10 + x * 10) = 4(5x + -10) (-10 + 10x) = 4(5x + -10) Reorder the terms: -10 + 10x = 4(-10 + 5x) -10 + 10x = (-10 * 4 + 5x * 4) -10 + 10x = (-40 + 20x) Solving -10 + 10x = -40 + 20x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-20x' to each side of the equation. -10 + 10x + -20x = -40 + 20x + -20x Combine like terms: 10x + -20x = -10x -10 + -10x = -40 + 20x + -20x Combine like terms: 20x + -20x = 0 -10 + -10x = -40 + 0 -10 + -10x = -40 Add '10' to each side of the equation. -10 + 10 + -10x = -40 + 10 Combine like terms: -10 + 10 = 0 0 + -10x = -40 + 10 -10x = -40 + 10 Combine like terms: -40 + 10 = -30 -10x = -30 Divide each side by '-10'. x = 3 Simplifying x = 3
| 8m+7=-41 | | 2(x-5)-4(2x-3)=16 | | 3k+5=k-3 | | 12-4x+14=6 | | 4x+2=-7+2x+19 | | 5-2x+-4x+9= | | 144t^4/36t | | -8k-3(2k-8)=94 | | 26t-9t^2=0 | | 19m-8-11m+15=41 | | 7385-67x=6453 | | 8w+24=-4(w+6) | | 12=7x-5 | | (X+9)(x+9)=12 | | 117c-13-14=115c+13 | | (10+6)/2 | | 10m-4m=8m-8 | | 8/4/1/2 | | 4x+12=6x+60 | | -1+2(-5r-6)=-83 | | (x-8)=9 | | 4x-y=3y+7,x+8y=4 | | 4x+12=6x-60 | | -3+b=4 | | -5v+3(v+6)=26 | | -3n=3 | | 9x-24=10x | | (9x+8)(8+x)=(x+5)(9x+8) | | 142+x=3x+64 | | 10+6/2 | | 20x-22y=58 | | 5/3p^2-3/p |